Left atrial strain time integral evaluated by two-dimensional speckle tracking predicts left atrial appendage dysfunction in patients with acute ischemic stroke - Takahata, Aoi; Watanabe, Tetsu; Wanezaki, Masahiro; Nagai, Takayuki; Edamura, Shunsuke; Tsuchiya, Hayato; Tamura, Harutoshi; Nishiyama, Satoshi; Otaki, Yoichiro; Kutsuzawa, Daisuke; Kato, Shigehiko; Arimoto, Takanori; et al. (Heart and vessels, 2024)
Cardioembolic stroke is a serious disease with poor prognosis, whose main embolic source is the left atrial appendage (LAA). Left atrial (LA) strain evaluated by the two-dimensional (2D) speckle tracking technique has been proposed. However, the commonly used peak LA strain reflects only LA reservoir function. The LA strain also includes indicators of the other LA functions, such as booster pump function, which reflects active contraction of the LA. This study aimed to investigate whether a newly developed parameter, the left atrial strain time integral (LASTI), can evaluate LAA dysfunction more accurately in patients with acute stroke. We measured LA strain using a 2D speckle tracking method in 168 patients with acute stroke and 20 age-matched control subjects. LASTI was calculated as the area under the LA strain curve in one cardiac cycle. LAA dysfunction was defined as LAA thrombus and/or severe spontaneous echo contrast by transesophageal echocardiography. LASTI was significantly lower in patients with LAA dysfunction than those without. LASTI was a better correlation with LAA blood flow velocity measured by transesophageal echocardiography than peak LA strain. Multivariate logistic regression analysis showed that LASTI was an independent predictor of LAA dysfunction after adjustment for conventional risk factors. LASTI can be a feasible parameter for predicting LAA dysfunction in patients with acute stroke.